Hypoxia triggers high-altitude headache with migraine features: A prospective trial. (July 2016) - Broessner, Gregor; Rohregger, Johanna; Wille, Maria; Lackner, Peter; Ndayisaba, Jean-Pierre; Burtscher, Martin
Background: Given the high prevalence and clinical impact of high-altitude headache (HAH), a better understanding of risk factors and headache characteristics may give new insights into the understanding of hypoxia being a trigger for HAH or even migraine attacks. Methods: In this prospective trial, we simulated high altitude (4500 m) by controlled normobaric hypoxia (Fi O2 = 12.6%) to investigate acute mountain sickness (AMS) and headache characteristics. Clinical symptoms of AMS according to the Lake Louise Scoring system (LLS) were recorded before and after six and 12 hours in hypoxia. O2 saturation was measured using pulse oximetry at the respective time points. History of primary headache, especially episodic or chronic migraine, was a strict exclusion criterion. Findings: In total 77 volunteers (43 (55.8%) males, 34 (44.2%) females) were enrolled in this study. Sixty-three (81.18%) and 40 (71.4%) participants developed headache at six or 12 hours, respectively, with height and SpO2 being significantly different between headache groups at six hours ( p < 0.05). Binary logistic regression model revealed a significant association of SpO2 and headache development ( p < 0.05, OR 1.123, 95% CI 1.001–1.259). In a subgroup of participants, with history of migraine being a strict exclusion criterion, hypoxia triggered migraine-like headache according to the International Classification of Headache Disorders (ICHD-3 beta) in n = 5 (8%) or n = 6 (15%), at six and 12 hours, respectively. Interpretation: Normobaric hypoxia is a trigger for HAH and migraine-like headache attacks even in healthy volunteers without any history of migraine. Our study confirms the pivotal role of hypoxia in the development of AMS and beyond that suggests hypoxia may be involved in migraine pathophysiology.